Dry haus / Nur Syafiqah Rosli ... [et al.] - Rosli, Nur Syafiqah; Suhaimy, Nur Syahirah; Isman Ismail, Nur Humairah Athirah; Zainal, Nur Syazrena Amyza; Juzarnor, Nur Syarafana (2019)
This business include five partnerships who play very important roles each in the company. The business capital is RM 50,000 which obtained from each of our partnership . THE DR Y HAUS ENTERPRISE product is the only product that can only be found in Bandar Seri Alam , Johar . Our product is an automatic drying rack which is very rare from all of the cloths line . Our product consists an automatic roof and rain censor. This product will be sold at our shop which is located in Jalan Lembah 19 , ground floor shop Bandar seri Alam, 81750 Masai, Johar. Our company product is based on how to manage the wet clothes that are sun dried when you are busy without worrying about the weather and spaces . We introduce this products through the social media such as facebook , twitter , instagram and also in the hotline call . The twenty first buyers will get special offers from us . The feedback from the customers will be considered to improve our products . Our product functions are to provide enough space for the wet clothes , smooth movement to change drying rack position and protection for the wet clothes from uncertain weather. The aim of producing this product is to make the customers to dry their clothes easier and to get the clothes dry in a short period of time without any interruption. The automatic drying rack which includes automatic roof and water censor will eliminate the worry of the customers when the weather is unpredictable as the roof will automatically switched on when the water censor detect even a droplet of water . The customers do not have to hesitate to move the dying rack to a shady place. If they want to do so , the automatic suspension is easy to move and light as is has four wheels and are made of from light steel that make the movement really smooth . This product also consists a durable iron rust . The rugs will not rust and will be last longer . It is very costly as the customers only have to buy it for once . We hopes that our business will be successful and we are dreaming to create victory in the name of Malaysia all over the world . Based on the MARA'S loan and the donations from each of the partnerships we will try our very best to make our dreams comes true . We also want to expend our business all over the states in Malaysia and be the well-known company . We hopes that our profit will increase through the years as we will do improvement to the product according to the customers' feedback.